Review Article: Synthesis of Fe3O4 Nanoparticle and Its Application for Glassy Carbon Electrode Modification - Agung Slamet Nugraha; Asep Bayu Dani Nandiyanto (Chimica et Natura Acta, 2021)
Nanomaterials have various unique properties and characteristics so that they can apply in many sectors. One of the most popular nanoparticles today is magnetite nanoparticles. Magnetite particles have several properties such as being super magnetic, having a high saturation field, chemical stability, biocompatibility, and low production costs. The purpose of this article is to review the synthesis of magnetite nanoparticles and their application to Glassy Carbon Electrode (GCE) modification. This modified GCE can applied as an electrochemical sensor to detect various organic and inorganic substances. In this study, type synthesis methods of magnetite nanoparticles which taken from kind literature well investigation include coprecipitation, sol-gel, microemulsion, hydrothermal, and thermal decomposition. The five routes have their respective advantages and disadvantages. Then the nano magnetite made can applied to modify the GCE as an electrochemical sensor that can detect uric acid, bacteria, and even metals dissolved in water.